Enhanced Cyanide Oxidation to Cyanate via Photocatalytic Ozonation: Comparing Sol–Gel and Hydrothermal Synthesis of BiVO4 Catalysts - Johan A. Vargas-Rueda; Alejandro R. Alonso; Rosa M. Luna-Sánchez; L. Lartundo-Rojas; Román Cabrera-Sierra (Water, Air, & Soil Pollution, 2024)
Bismuth vanadate has been reported as a promising active semiconductor for visible light harvesting. However, the rapid recombination of charge carriers has limited its photocatalytic properties. As an alternative route to treat contaminated water containing cyanide ions, photoactivated BiVO 4 in combination with ozone has been investigated. BiVO 4 photocatalysts were synthesized by microwave-assisted hydrothermal method, as well as by sol–gel, obtaining the monoclinic crystalline structure and a band gap of ~ 2.5 eV by XRD and UV–Vis DRS. The morphological analysis, elemental chemical composition, BET surface area, stability, and photoluminescence characteristics were carried out for both samples. Although the majority composition belongs to BiVO 4 , the presence of secondary phases was confirmed by XPS. The BiVO 4 obtained by sol–gel (sol–gel BVO) exhibited superior photocatalytic performance with a lower reaction time (15 min) to oxidize free cyanide under visible-light radiation in combination with ozone. The degradation kinetics is described by pseudo-zero-order kinetics, and the rate constant (k 0 ) of BiVO 4 synthesized by microwave-assisted hydrothermal method was found to be the lower of the two. The high efficiency of the photocatalytic ozonation for the removal of free cyanide can be ascribed to a combination of two oxidation systems and the synergy of both processes.